ART AND MORALITY IN THE CONTEXT OF FORMATION SPIRITUAL NEEDS AND INTERESTS (Pedagogy of Higher and Secondary Education, 2008)
In the article attempt was undertaken to show the process when by the help of art one can affect (positively) not only on moral and mental sphere of growing up man but even on formation of one's interests and needs.